Efektivitas Metode Drill terhadap Peningkatan Teknik Dasar Renang Gaya Dada - Latuheru, Ricardo V. (Jurnal Inovasi Olahraga, 2026)
Purpose of the study: This study aims to examine the effectiveness of the drill method in improving the basic technique of breaststroke swimming among beginner swimmers in Makassar.Materials and methods: The research method employed a pretest-posttest control group design with 40 participants aged 10-14 years who were divided into experimental group (n=20) and control group (n=20). The experimental group received drill method training for 12 sessions (3 times per week for 4 weeks), while the control group followed conventional swimming lessons. Data collection used a breaststroke technique rubric consisting of five indicators: body position, arm movement, leg movement, breathing, and coordination, assessed by two certified swimming coaches. Data were analyzed using paired sample t-test and independent sample t-test with significance level of p